Trans-Cinnamaldehyde, Carvacrol, and Eugenol Reduce Campylobacter jejuni Colonization Factors and Expression of Virulence Genes in Vitro - Upadhyay, Abhinav; Arsi, Komala; Wagle, Basanta R.; Upadhyaya, Indu; Shrestha, Sandip; Donoghue, Ann M.; Donoghue, Dan J. (Frontiers in Microbiology, 2017)
Campylobacter jejuni is a major foodborne pathogen that causes severe gastroenteritis in humans characterized by fever, diarrhea and abdominal cramps. In the human gut, Campylobacter adheres and invades the intestinal epithelium followed by cytolethal distending toxin mediated cell death, and enteritis. Reducing the attachment and invasion of Campylobacter to intestinal epithelium and expression of its virulence factors such as motility and cytolethal distending toxin (CDT) production could potentially reduce infection in humans. This study investigated the efficacy of sub-inhibitory concentrations (SICs, concentration not inhibiting bacterial growth) of three GRAS (generally recognized as safe) status phytochemicals namely trans-cinnamaldehyde (TC; 0.005, 0.01%), carvacrol (CR; 0.001, 0.002%) and eugenol (EG; 0.005, 0.01%) in reducing the attachment, invasion, and translocation of C. jejuni on human intestinal epithelial cells (Caco-2). Additionally, the effect of these phytochemicals on Campylobacter motility and CDT production was studied using standard bioassays and gene expression analysis. All experiments had duplicate samples and were replicated three times on three strains (wild type S-8, NCTC 11168, 81-176) of C. jejuni. Data were analyzed using ANOVA with GraphPad ver. 6. Differences between the means were considered significantly different at P<0.05. The majority of phytochemical treatments reduced C. jejuni adhesion, invasion, and translocation of Caco-2 cells (P<0.05). In addition, the phytochemicals reduced pathogen motility and production of cytolethal distending toxin in S-8 and NCTC 11168 (P<0.05). Real-time quantitative PCR revealed that phytochemicals reduced the transcription of select C. jejuni genes critical for infection in humans (P<0.05). Results suggest that TC, CR, and EG could potentially be used to control C. jejuni infection in humans.